2016
DOI: 10.1016/j.envpol.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in terrestrial forested systems with highly elevated mercury deposition in southwestern China: The risk to insects and potential release from wildfires

Abstract: a b s t r a c tForests are considered a pool of mercury in the global mercury cycle. However, few studies have investigated the distribution of mercury in the forested systems in China. Tieshanping forest catchment in southwest China was impacted by mercury emissions from industrial activities and coal combustions. Our work studied mercury content in atmosphere, soil, vegetation and insect with a view to estimating the potential for mercury release during forest fires. Results of the present study showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 70 publications
4
51
1
Order By: Relevance
“…Litterfall THg deposition was statistically higher at the refoliation period in spring (February to May) compared to other seasons (June to January) in the broad‐leaved forest ( p < 0.05; Figure ) because of higher litterfall mass and concentration. The higher concentrations in the litterfall were observed at the refoliation period because the ratio of leaf in the litterfall was higher during this period and leaf had significant higher mercury concentrations compared to other components (e.g., twigs, fruit, and bark; Zhou et al, ; Zhou et al, ). Our previous study reported the observation of litterfall mercury in the same forest, and Z. W. Wang et al () observed that annual THg deposition by litterfall was up to 292 μg/m 2 , which was sixfold higher than that presented in this study.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Litterfall THg deposition was statistically higher at the refoliation period in spring (February to May) compared to other seasons (June to January) in the broad‐leaved forest ( p < 0.05; Figure ) because of higher litterfall mass and concentration. The higher concentrations in the litterfall were observed at the refoliation period because the ratio of leaf in the litterfall was higher during this period and leaf had significant higher mercury concentrations compared to other components (e.g., twigs, fruit, and bark; Zhou et al, ; Zhou et al, ). Our previous study reported the observation of litterfall mercury in the same forest, and Z. W. Wang et al () observed that annual THg deposition by litterfall was up to 292 μg/m 2 , which was sixfold higher than that presented in this study.…”
Section: Resultsmentioning
confidence: 96%
“…The monthly litterfall productions ranged from 11 ± 3 to 72 ± 12 g/m 2 and from 11 ± 4 to 181 ± 23 g/m 2 for coniferous and broad‐leaved forests, respectively, and annually averaged 475 ± 23 and 1018 ± 59 g/m 2 . The litterfall biomass was lower than that in tropical areas, comparable to subtropical areas and higher than temperate areas (X. Wang, Bao, et al, ; Zhou et al, ). Additionally, X. Wang, Bao, et al () reviewed 858 litterfall biomass around the world, which averaged 821 ± 83 g · m −2 · year −1 in Brazil, 1,192 ± 576 g · m −2 · year −1 in China, and 200 ± 145 g · m −2 · year −1 in North America and Europe, and found that litterfall biomass was the main reason behind the difference in litterfall Hg fluxes of different regions rather than the Hg concentration in litter.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to the shortage of water resource in semiarid and arid zones, treated wastewater has been an important source of irrigation water for agriculture in Tianjin and has been used as such for at least 45 years. Additionally, large quantities of coal was burned to maintain the normal operation of city (Wu et al 2011), which emitted large amount mercury to the atmosphere and then deposited to the terrestrial and aquatic ecosystems (Zhou et al 2016). The aim of this study was to investigate the pollution status, accumulation and fractionation of mercury in the sediments and soils collected from two representative sites in Tianjin, China.…”
mentioning
confidence: 99%
“…Mercury is easy to be absorbed by skin, respiratory and digestive tract, and to be accumulated in the body, which could damage the structure of protein and take a toll on kidney and liver. 3,4 To monitor the concentration of Hg…”
Section: Introductionmentioning
confidence: 99%